Perioperative blood loss is a risk factor for postoperative delirium in geriatric hip fracture patients: a retrospective study - Deng, Yubo; Zhang, Tianqin; Xie, Hu; Zeng, Jingshan (Frontiers in Medicine, 2025)
BackgroundPostoperative delirium (POD) is a common and serious complication in elderly patients with hip fractures and is associated with adverse outcomes. The aim of this study was to investigate perioperative blood loss as a potential risk factor for POD.MethodsThis retrospective cohort study included electronic medical records of hip fracture patients admitted to Yichang Second People’s Hospital from January 2020 to June 2024, with a total of 247 patients. POD was diagnosed using the Confusion Assessment Method (CAM) on the basis of the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) criteria. Perioperative blood loss was calculated using the Gross linear equation for red blood cell volume, and preoperative blood volume (PBV) was estimated using the Nadler formula. Univariate and multivariate logistic regression analyses were performed to identify independent risk factors for POD.ResultsThe incidence of POD was 39.7% (98/247). Multivariate analysis revealed that increased intraoperative blood loss (OR: 6.017, 95% CI: 3.325–10.887, p < 0.001), prolonged surgical duration (OR: 1.072, 95% CI: 1.045–1.101, p < 0.001), history of coronary heart disease (OR: 3.175, 95% CI: 1.546–6.519, p = 0.002), and history of cerebral infarction (OR: 3.170, 95% CI: 1.546–6.497, p = 0.002) were independent risk factors for POD. Binary logistic regression revealed a significant dose–response relationship between blood loss and POD susceptibility (all p < 0.05). No significant associations were found with age, sex, or BMI.ConclusionThis study confirms that perioperative blood loss is an independent and modifiable risk factor for POD in elderly hip fracture patients. On the basis of these findings, optimizing perioperative management—such as reducing intraoperative blood loss and shortening surgical duration—may serve as an effective strategy to lower the incidence of POD in this population.